On g-factor experiments with individual ions - Sturm, Sven; Blaum, Klaus; Schabinger, B.; Wagner, A.; Quint, Wolfgang; Werth, G. (Journal of physics. B, Atomic, molecular and optical physics, 2010)
Individual hydrogen- and lithium-like ions with medium nuclear charge Z are confined in a cylindrical triple Penning trap for nearly unlimited time under well-controlled conditions in a small volume in space. We present progress in a project to determine the magnetic moment of the electron bound in Si13+ and Ca19+ and their Li-like counterparts. This serves for testing bound-state quantum electrodynamic calculations. Significant technical improvements will allow for higher precision than in the previous similar experiments on C5+ and O7+.